(untitled) (Applied Biological Research, 2020)
Seven paddy cultivars viz., ‘ADT 38’, ‘ADT(R) 46’, ‘CO 43’, ‘CO(R) 50’, ‘CR 1009’, ‘IW Ponni’ and ‘Swarna’ were assessed for deterioration pattern during natural and artificial ageing. Various physiological and biochemical attributes associated with seed deterioration were studied in relation to seed vigour. Decline in dehydrogenase, α-amylase, catalase, peroxidase, superoxide dismutase activities and increase in electrical conductivity of seed leachate were observed during natural ageing. The deterioration during artificial ageing (400C temperature and 100% relative humidity) followed the same pattern but with accelerated rate. The disintegration of embryo and aleurone layer was also conspicuous in accelerated aged seeds. These biochemical changes occurring during ageing are quite well reflected in terms of physiological attributes like loss of viability and vigour. Among the evaluated paddy cultivars, ‘CR 1009’ proved superior over all the other cultivars in maintaining higher viability and vigour potential while cv. ‘ADT 38’ and ‘ADT(R) 46’ showed poor storability.